MERGER AND FINANCIAL PERFORMANCE : ISLAMIC BANKS PERSPECTIVE - Farhana, Bibi Faiza; Tsaqyfa, Mazaya Najmy; As’adi, Firda Rizqi Amalia; Canggih, Clarashinta; Nurafini, Fira (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The growth of the Islamic Finance Industry shows positive developments. This study analyzes what influences performance in Islamic banking using quarterly data from 2018-2023. The research method used in this study is quantitative research with a comparative approach to compare financial performance consisting of CAR, ROA, ROE, NPF, NI, NOM, BOPO, and FDR of each Islamic Commercial Bank. The data obtained is then tested using SPSS. Before the analysis test is carried out, a normality test is first carried out as a basis for determining the appropriate comparative test analysis. If all data is normally distributed, the One Way Anova method is used, while the Kruskal Wallis Test is used if the data is not normally distributed. The results of the analysis test are used to see if there is a statistically significant difference between two or more variables. In this study, there are differences in financial performance between Islamic banks in Indonesia, including Bank Muamalat, Bank Mega Syariah, Bank Victoria Syariah, Bank Panin Dubai Syariah, Bank KB Bukopin Syariah, Bank BCA Syariah, Bank BPTN Syariah, Bank BJB Syariah, Bank Aceh. This study uses secondary data from quarterly financial reports reported to the Financial Services Authority (OJK) from 2018 to 2023.